Nabi Muhammad Sebagai Role Model Dalam Penanaman Akhlak Remaja Muslim Milenial (Kajian Al-Qur’an Surat Al-Ahzab Ayat 21) - Sulistyowati Sulistyowati; Ahmad Faizun; Fatkhurrohman (DAS Institute, 2024)
Every human being needs an example in his life, Allah has set an example of goodness in the Prophet Muhammad SAW for all his people. The Prophet Muhammad became a role model for teachers and parents in shaping a child's morals. The problem studied is looking for the concept of a role model in the Prophet Muhammad SAW in cultivating easy morals. As well as looking for the results of contextualizing role models in the Prophet Muhammad SAW in cultivating easy morals according to QS. Al-Ahzab verse 21. The approach used is qualitative research with the type of library research. Data sources were obtained from primary and secondary data sources related to research. The data analysis technique used is content analysis, which is basically a systematic technique for analyzing message content and processing messages, or a tool for observing and analyzing the open communication behavior of selected communicators. Apart from that, it also uses discourse analysis which is one way of studying the meaning of messages as a result of the limitations of content analysis and other alternatives due to the limitations of content analysis. The results of the research show that there are commands for believers to imitate the Prophet, such as patience, strength, heroism, fighting, and hope for help from His God, as was the case during the Ahzab war. These attitudes can be used as role models for teachers and parents in shaping a child's morals.